INDIA BANGLADESH RELATIONS : A STUDY OF ENVIRONMENTAL ASPECT (International Journal of Food and Nutritional Sciences, 2022)
The Ganga Brhamaputra Meghna basin made the geographical area of the eastern part of India and Bangladesh. A river network and the world’s largest mangrove forest are the integral part of these two countries. Environmental interdependence shaped by geographical position make a common platform. So environmental issues became integral part of India Bangladesh relations. Impact of barrages on nature, hydro environmental issues, Sundarban as common ecological asset, effect of natural hazards, impact of climate change, losses of lives and livelihood due to natural hazards etc. are the defining features of environmental aspect of India Bangladesh relations. From the end of 20th Century a new trend of interaction based on environmental issues among these countries and its peoples started. After being bilateral issue this trend added a new paradigm of international as well as neighbourhood relation. Their policy became regional policy on this matter. To face the challenging situation two nations have engaged in to adopt collaborative measures to resolve water-related issues, to find a fair and sustainable solution. Joint efforts have been taken to protect the Sundarban, and its biodiversity. The environmental aspect of India Bangladesh relations became dynamic with contemporary challenges, environmental concerns with broader socio-economic policies and collaborative measures. Environment related MOU’s have been signed between the government of two these countries. BI-SRCI support effective bilateral cooperation in the Sundarban Regions. This paper aims to provide an overview on environmental issues and dynamics of India Bangladesh relations.